Environmental impacts of the agricultural colonization in Coto Brus, Costa Rica (1940-2018) - Quesada-Román, Adolfo; Díaz-Bolaños, Ronald (Revista Geográfica de América Central., 2019)
Coto Brus is a canton in southeast Costa Rica, serving as a melting pot of indigenous, Costa Rican, Panamanian and Italian cultures that shaped their territory during the last seventy years. The objective of this paper is to analyze the environmental impact of the agricultural colonization of Coto Brus and the resulting changes in the territory’s landscape experienced since 1940. This study exposes the other side of the explosive development that took place in Coto Brus during its first decades of existence as a canton and also highlights how multicultural patterns deprived the growth of the agricultural frontier in one of the least studied regions of the country. The methodology is based on literature review of different bibliographical sources such as books, articles, historical accounts and legislation. By means of a historical geographical analysis, three historical periods were determined which synthesize the environment impacts brought by productive activities for more than seven decades.